Composite protective coating, preparation method of composite protective coating, alloy film product and application of alloy film product

By preparing a composite protective coating on the surface of the aluminum alloy, combining Ni-P and Cr-Zr-N materials, the corrosion resistance and aesthetics of the aluminum alloy materials are solved, and efficient protection and aesthetic effects are achieved.

CN119685821APending Publication Date: 2025-03-25VITALINK INDUSTRY (SHENZHEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311245596.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Due to its weak corrosion resistance, easy corrosion, and uneven surface polishing, aluminum alloy materials affect their aesthetic effect, limiting their application in lightweight materials.

Method used

A composite protective coating, including a first interface layer containing Ni-P material and a second interface layer containing Cr-Zr-N material, is prepared by electroless coating and vapor deposition technology to ensure high corrosion resistance and flatness of the coating.

Benefits of technology

The coating is achieved with high corrosion resistance and smoothness, which improves the aesthetics of the product, and enhances the stability of the coating by blocking the release of nickel elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685821A_ABST
    Figure CN119685821A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of surface coatings, in particular to a composite protective coating, a preparation method of the composite protective coating, an alloy film product and application of the alloy film product. The composite protective coating comprises a first interface layer containing a Ni-P material and a second interface layer containing a Cr-Zr-N material. The composite protective coating disclosed by the invention has the characteristic of high corrosion resistance, and meanwhile, the smoothness of the surface of the coating can be ensured, so that a product has the characteristic of attractive appearance; and meanwhile, the nickel release blocking effect of the nickel-containing coating can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface coatings, and in particular to a composite protective coating and a preparation method thereof, and an alloy film product and application thereof. Background Art

[0002] With the development of science and technology, "3C products" are gradually moving towards lightweight, and products such as automotive parts and aerospace parts are also gradually moving towards lightweight. Given that aluminum alloy materials have lower costs and lighter textures, they have great application potential in lightweighting. Among them, "3C products" are a general term for computer, communication and consumer electronic products, also known as "information appliances", such as computers, tablets, mobile phones or digital audio players. Since 3C products are generally not large in size, they are often collectively referred to as "3C small appliances".

[0003] At present, aluminum alloy materials have gradually become one of the main raw materials for 3C products. For example, among the existing metal parts in the mobile phone field, aluminum alloy products are often used in the middle frame of mobile phones. However, due to the weak corrosion resistance of aluminum alloy materials, it is easy to corrode during use. Nickel itself has extremely high chemical stability and is often used as an anti-corrosion material on the surface of aluminum alloys. However, since nickel is allergenic, nickel is the most common allergenic material in Europe, which also limits the application of nickel materials in protective coatings. At the same time, due to its low hardness and high plasticity, aluminum alloys have uneven polishing on the surface, which affects the aesthetic effect of the aluminum alloy surface. These problems make it impossible for aluminum alloy materials to be directly used as lightweight materials for the above-mentioned products, and it is necessary to add a coating on the surface for protection and modification.

[0004] Therefore, it is necessary to develop coating materials with good corrosion resistance and smoothness. Summary of the invention

[0005] An object of the present invention is to provide a composite protective coating having high corrosion resistance and capable of ensuring the smoothness of the coating surface.

[0006] Another object of the present invention is to provide a method for preparing the composite protective coating.

[0007] Another object of the present invention is to provide application of the composite coating in alloy film products.

[0008] Another object of the present invention is to provide an alloy film product, including a composite protective coating.

[0009] In order to achieve the above-mentioned object of the present invention, the present invention provides a composite protective coating, including a first interface layer containing Ni-P material and a second interface layer containing Cr-Zr-N material.

[0010] In some embodiments, the chemical formula of the Ni-P material is Ni 1-x P x , where 7%≤x≤12%, and x is the mass percentage.

[0011] In some embodiments, the ratio of the diffuse reflectivity value of the first interface layer to the total reflectivity is P Rd ≤5%.

[0012] In some embodiments, the chemical formula of the Cr-Zr-N material is (Cr a Zr b N c )M y , M is a doping element, wherein a, b, c and y are each independently an atomic ratio, wherein a and b are positive numbers between 0 and 100, c≤55.1, and 0≤y / (a+b+c+y)≤0.05, a+b+c+y=100.

[0013] In some embodiments, 4.7≤c≤55.1.

[0014] In some embodiments, the thickness of the first interface layer is 0.5-10 μm; the thickness of the second interface layer is 0.05-6 μm.

[0015] In some embodiments, the composite protective coating further includes a third interface layer; the third interface layer is a decorative coating; in the composite protective coating, the first interface layer, the second interface layer and the third interface layer are arranged in sequence.

[0016] In some embodiments, the third interface layer includes a material containing at least one of Ti, Cr, Si and W. Further, the material is at least one of a simple substance, a nitride, a carbide and a carbonitride.

[0017] Another aspect of the present invention provides a method for preparing a composite protective coating, comprising the following steps:

[0018] Forming a first interface layer on at least a portion of the surface of the substrate by chemical plating;

[0019] The constituent elements of the second interface layer are deposited on at least a portion of the surface of the first interface layer by vapor deposition to form the second interface layer.

[0020] In some embodiments, the vapor deposition is physical vapor deposition. Further, the physical vapor deposition includes: under the condition of introducing a mixed gas of argon gas and nitrogen-containing gas, using a combination of a chromium target and a zirconium target, a chromium-zirconium alloy target or a chromium-zirconium-nitrogen alloy target, sputtering and depositing the second interface layer on at least a portion of the surface of the first interface layer.

[0021] In some embodiments, the sputtering deposition conditions include at least one of the following features:

[0022] (1) The temperature of sputtering deposition is 30-330°C;

[0023] (2) The total gas pressure of the mixed gas is 0.3-1.2 Pa;

[0024] (3) The nitrogen-containing gas is nitrogen gas, and the gas flow rate of the nitrogen gas is 5 to 52 sccm;

[0025] (4) The nitrogen-containing gas is nitrogen, and the gas volume ratio of argon to nitrogen in the mixed gas is (2-6):1;

[0026] (5) When the target material is a combination of a chromium target and a zirconium target, the power density of the chromium target is 1.3 to 6.7 W / cm 2 The power density of the zirconium target is 0.5~7.9W / cm 2 ;

[0027] (6) When the target material is a chromium-zirconium alloy target or a chromium-zirconium-nitrogen alloy target, the power density of the target material is 4 to 6 W / cm 2 ;

[0028] (7) The bias voltage of the substrate is -150 to -20 V;

[0029] (8) The sputtering deposition time is 10 to 150 minutes;

[0030] (9) The background vacuum of the vacuum chamber used for sputtering deposition is ≤3.0×10 -4 Pa.

[0031] In some embodiments, after forming the first interface layer and before forming the second interface layer, the method further includes: performing a polishing process on the surface of the first interface layer. Furthermore, during the polishing process, the surface glossiness of the first interface layer is ≥500 GU.

[0032] In some embodiments, the preparation method further comprises: depositing constituent elements of the third interface layer on at least a portion of the surface of the second interface layer by vapor deposition to form the third interface layer.

[0033] In some embodiments, the method for forming the third interface layer specifically includes: under the condition of introducing a mixed gas of nitrogen-containing gas and / or carbon-containing gas and argon gas, using a metal single target or an alloy target, sputtering and depositing on at least a portion of the surface of the second interface layer to form the third interface layer.

[0034] Another aspect of the present invention provides the use of any one of the above-mentioned composite protective coatings in alloy film products.

[0035] In some embodiments, the composite protective coating is used as at least a portion of a protective coating of an alloy film product.

[0036] Another aspect of the present invention provides an alloy film product, comprising a substrate and any one of the above-mentioned composite protective coatings.

[0037] In some embodiments, the composite protective coating is located on at least one side of the substrate.

[0038] In some embodiments, the surface material of the substrate is a light alloy or a pure metal. Further, the light alloy includes at least one of nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based and zinc-based; the pure metal includes at least one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) The composite protective coating of the present invention has high corrosion resistance and can ensure the flatness of the coating surface, so that the product has aesthetic characteristics; at the same time, the present invention can achieve the nickel release blocking effect of the nickel-containing coating;

[0041] (2) The composite protective coating of the present invention can be directly applied to the surface of a substrate such as an aluminum alloy, or can be used together with other coatings as a transition layer between the substrate such as an aluminum alloy and other coatings, thereby giving the alloy film product excellent corrosion resistance and aesthetics;

[0042] (3) The preparation method of the composite protective coating of the present invention is easy to operate, green and environmentally friendly, and has the advantages of being quantifiable, highly efficient, and having good repeatability, and is suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 A schematic diagram of the cross-sectional structure of a composite protective coating (including a substrate) provided in an embodiment of the present invention;

[0045] Figure 2 A schematic diagram of the structure of a device for preparing a second interface layer and a third interface layer provided in an embodiment of the present invention;

[0046] Figure 3 The SEM image of the aluminum alloy substrate bare chip provided for Comparative Example 2;

[0047] Figure 4 This is a SEM image of the aluminum alloy sample provided for Comparative Example 6 of the present invention.

[0048] Reference numerals:

[0049] 1- vacuum chamber; 2- sample stage; 3- DC anode;

[0050] 4-first target; 5-second target. DETAILED DESCRIPTION

[0051] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0052] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0053] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0054] Aluminum alloy materials have low cost and are easy to process. They are often used as the preferred material for various metal products. However, aluminum alloy materials have the problems of strong plasticity and low hardness, which directly leads to their poor polishability. Specifically, aluminum alloy is uneven after polishing and has low gloss, which affects its aesthetics. At the same time, aluminum alloy materials are easily corroded and have poor corrosion resistance. Such problems directly affect the further large-scale application of aluminum alloy materials.

[0055] Based on this, the present invention provides a composite protective coating, including a first interface layer containing a Ni-P material and a second interface layer containing a Cr-Zr-N material.

[0056] In order to solve the problem of polishability of aluminum alloy surface, it is achieved by improving the hardness and density of aluminum alloy surface. The inventors have found through a lot of research and experiments that Ni-P material is most suitable for the surface of substrates such as aluminum alloys. This is because: Ni-P material has high density and high hardness, which can effectively increase the hardness and density of the surface of substrates such as aluminum alloys, thereby increasing the polishability of the substrate. After the Ni-P coating is formed on the substrate surface, it can be further polished and polished to obtain a smoother substrate. After obtaining a smooth first interface layer, it is more conducive to the second interface layer tending to grow smoothly.

[0057] However, since nickel is a common allergenic material, it cannot be directly used as a protective coating in the prior art. Therefore, the present invention also provides a second interface layer containing Cr-Zr-N material on the surface of the first interface layer containing Ni-P material. Through a large number of experimental analyses, the inventors found that Cr-Zr-N material can effectively block the release of Ni element of Ni-P material in the first interface layer. On the one hand, the Zr element in Cr-Zr-N has a very strong chemical affinity with the Ni element, so that the Ni in the first interface layer and the Zr in the second interface layer have a strong chemical bonding effect; on the other hand, the Cr-Zr-N material has a certain high density; the combination of the two aspects makes it impossible for the Ni element released from the first interface layer to precipitate under the protection of the second interface layer with high chemical affinity and high density, thereby blocking the release of Ni element to the outside. At the same time, the high chemical affinity further enhances the bonding force between the first interface layer and the second interface layer. In addition, Cr and Zr are both strongly inert metals, and the alloy compound formed has the characteristics of high density and high inertness, which can effectively improve the corrosion resistance of the coating.

[0058] In the Cr-Zr-N material of the second interface layer of the present invention, Cr and Zr are easy to form a strong bond energy, which is conducive to the rapid growth of the Cr-Zr alloy during the deposition process. The addition of nitrogen further promotes the re-nucleation of the Cr-Zr alloy to form the Cr-Zr-N material of the present invention, improves the density of the nucleation of the second interface layer, and increases the blocking performance and corrosion resistance. Among them, in terms of atomic size, the Cr atomic radius is The atomic radius of Zr is The atomic radius of N is The atomic sizes of Cr and Zr are similar, while the atomic size of N is smaller. During the nucleation process, small-sized N atoms can penetrate into the pores of large-sized Cr and Zr metal grains with appropriate atomic ratios, achieving a better pore-filling effect and making the atomic arrangement denser, thereby better improving the blocking and corrosion resistance of the coating.

[0059] Among them, the protection time of the second interface layer Cr-Zr-N of the present invention in the salt spray corrosion resistance test is ≥8 hours, and the protection time of the composite protective coating composed of the Ni-P material and the Cr-Zr-N material of the present invention in the salt spray corrosion resistance test is ≥48 hours (using the ASTM B117 salt spray test method).

[0060] In some embodiments, the chemical formula of the Ni-P material is Ni 1-x P x , where 7%≤x≤12%, and x is the mass percentage.

[0061] For example, in different embodiments, in the Ni-P material, the mass percentage x of P can be selected from but not limited to 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12% or a range consisting of any two of them.

[0062] The inventors have found through research that when the P content in the Ni-P material is within the above range, it is a Ni-rich material, which can ensure that the Ni-P material is in a stable state, while increasing the hardness and density of the substrate surface such as aluminum alloy, thereby increasing the polishability of the aluminum alloy, so that the flatness can be further improved through polishing.

[0063] In some embodiments, the ratio of the diffuse reflectance value of the first interface layer to the total reflectance value is P Rd ≤5%.

[0064] For example, in different embodiments, the ratio of the diffuse reflectivity value of the first interface layer to the total reflectivity is P Rd It can be ≤5%, further can be ≤4.5%, further can be ≤4%, further can be ≤3.5%, further can be ≤3%, further can be ≤2.5%, further can be ≤2%, further can be ≤1.5%, further can be ≤1%.

[0065] P Rd The smaller the value, the smoother the surface. The provision of the first interface layer of the present invention improves the polishability of the substrate, and the flatness and smoothness of the surface can be improved by polishing.

[0066] In some embodiments, the chemical formula of the Cr-Zr-N material is (Cr a Zr b N c )M y , M is a doping element, wherein a, b, c and y are each independently an atomic ratio, a, b, c are positive numbers between 0 and 100, c≤55.1, and 0≤y / (a+b+c+y)≤0.05, a+b+c=100.

[0067] In some embodiments, 4.7≤c≤55.1.

[0068] The Cr-Zr-N material of the present invention may or may not contain doping elements, and can be adjusted according to actual needs. It can be understood that in the present invention, when doping elements are contained, the type and amount of doping elements are limited to being able to form the Cr-Zr-N material of the present invention without affecting the excellent blocking property, corrosion resistance and high hardness.

[0069] The Cr-Zr-N material of the present invention mainly contains three elements: Cr, Zr and N. Furthermore, the sum of the atomic ratios of the three elements accounts for ≥95% of the sum of the atomic ratios of all elements in the Cr-Zr-N material, that is, 0≤y / (a+b+c+y)≤0.05, further such as ≥98% (0≤y / (a+b+c+y)≤0.02), and further =100%, that is, it does not contain doping elements.

[0070] When the Cr-Zr-N material has the above-mentioned element ratio, it is conducive to fully exerting the blocking effect, forming a denser structure, and obtaining better corrosion resistance. At this time, during the nucleation process, N atoms can penetrate into the pores of large-sized Cr and Zr metal grains, better achieve the pore filling effect, make the coating atoms stack more densely, and better improve the corrosion resistance of the coating.

[0071] In some embodiments, in the Cr-Zr-N material, when a, b, and c are positive numbers between 0 and 100, 4.7≤c≤55.1, and a+b+c=100, a can be selected from but not limited to 20, 30, 40, 50, 60, 70, 80, 82, or a range consisting of any two of them; b can be selected from but not limited to 7, 12, 15, 20, 30, 40, or a range consisting of any two of them; c can be selected from but not limited to 4.7, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55.1, or a range consisting of any two of them.

[0072] In some embodiments, the doping element is a non-metallic element and / or a metallic element. Further, the non-metallic element includes any one or more of O, C, B, Si and Ar; the metallic element includes any one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.

[0073] It should be noted that the Cr-Zr-N material of the present invention allows the presence of inevitable impurities introduced during the preparation process. "Inevitable impurities" are not intentionally added impurities, and the main reason for their existence is that they are accidentally introduced during the preparation process; non-limiting examples of "inevitable impurities" include, for example, elements such as C and O present in the air, and may also come from components in raw materials or equipment. The atomic content of "inevitable impurities" in Cr-Zr-N materials is usually trace or micro-amount, which can generally be ignored, such as less than 0.05% atomic content. Taking the technical solution of "Cr-Zr-N material is a Cr-Zr-N ternary alloy material composed of Cr, Zr and N elements" as an example, at this time, theoretically, the alloy coating is composed of three elements: Cr, Zr and N. However, trace or micro-amounts of other elements other than Cr, Zr and N may be introduced during the preparation process, such as C, O, etc.

[0074] In some embodiments, the thickness of the first interface layer is 0.5-10 μm; the thickness of the second interface layer is 0.05-6 μm.

[0075] For example, in different embodiments, the thickness of the first interface layer can be selected from but not limited to 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm or a range consisting of any two thereof; the thickness of the second interface layer can be selected from but not limited to 0.05μm, 0.08μm, 0.1μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm or a range consisting of any two thereof.

[0076] The thickness of the first interface layer is within the above range, which can effectively take into account the polishability of the obtained substrate, ensure the smooth shape of the first interface layer, and shorten the production cycle. The thicker the second interface layer is, the more conducive it is to improve the blocking effect on the nickel in the first interface layer, and improve the corrosion resistance. The second interface layer of the present invention can achieve blocking, corrosion resistance and shorten the production cycle at a relatively thin thickness.

[0077] In some embodiments, the composite protective coating further comprises a third interface layer; the third interface layer is a decorative coating; in the composite protective coating, the first interface layer, the second interface layer and the third interface layer are sequentially arranged. Figure 1 The cross-sectional structure diagram of the composite protective coating (including the substrate) shown in the figure, a first interface layer is formed on at least a portion of the surface of the substrate, a second interface layer is then formed on at least a portion of the surface of the first interface layer, and then a third interface layer is formed on at least a portion of the surface of the second interface layer.

[0078] The present invention sequentially arranges a first interface layer and a second interface layer on the surface of a substrate to obtain a flat, high-bonding, nickel-blocking and corrosion-resistant coating, and then further arranges a third interface layer on the surface of the second interface layer. Since the first interface layer provides flatness and the second interface layer increases the protective properties, the third interface layer tends to grow in a flat manner, thereby improving the glossiness of the third interface layer and further enhancing the aesthetic effect of the composite protective coating of the present invention.

[0079] In some embodiments, the third interface layer may include a single layer coating or a multilayer coating.

[0080] In some embodiments, the third interface layer includes a material containing at least one of Ti, Cr, Si, and W. Further, the material is at least one of a simple substance, a nitride, a carbide, and a carbonitride.

[0081] The material of the third interface layer of the present invention is selected from any single substance of Ti, Cr, Si and W, or any one or more compounds of Ti, Cr, Si and W or alloy compounds formed with other metals to form a coating with color characteristics. The single-layer coating or multi-layer coating in the third interface layer can be independently selected from the materials of the third interface layer to improve the applicability of the product. In addition, since the thermal expansion coefficients of metals such as Ti, Cr, Si, and W are close to those of Cr in the second interface layer, during the deposition process, the materials have high chemical stability, which makes the third interface layer of the present invention conducive to stable growth.

[0082] It can be seen from the above that the composite protective coating of the present invention, through the arrangement of three interface layers and the interaction between the interface layers, further improves the corrosion resistance and aesthetics on the surface of the substrate such as aluminum alloy.

[0083] Another aspect of the present invention provides a method for preparing a composite protective coating, comprising the following steps:

[0084] Forming a first interface layer on at least a portion of the surface of the substrate by chemical plating;

[0085] The constituent elements of the second interface layer are deposited on at least a portion of the surface of the first interface layer by vapor deposition to form the second interface layer.

[0086] In some embodiments, the chemical plating method includes chemical deposition. Further, in the chemical deposition, the deposition liquid used is a high-phosphorus nickel plating liquid, and a conventional commercial high-phosphorus nickel plating liquid can be used, such as the high-phosphorus nickel plating liquids produced by ATOTECH, with the grades of 1151A, 1151B and 1151C. In actual operation, the phosphorus content in the nickel plating liquid used for chemical plating is adjusted according to the phosphorus content in the Ni-P material of the first interface layer; when the target phosphorus content in the Ni-P material of the first interface layer is relatively high, the proportion of each high-phosphorus nickel plating liquid is adjusted to obtain a nickel plating liquid with a relatively high phosphorus content; when the target phosphorus content in the Ni-P material of the first interface layer is relatively low, the proportion of each high-phosphorus nickel plating liquid is adjusted to obtain a nickel plating liquid with a relatively low phosphorus content.

[0087] In some embodiments, the temperature of chemical deposition is 80-100°C.

[0088] In some embodiments, the vapor deposition is physical vapor deposition. Further, the physical vapor deposition can be achieved by any one or more of the following methods: vacuum evaporation, sputtering, arc plasma plating, ion plating and molecular beam epitaxy, such as magnetron sputtering.

[0089] In some embodiments, see Figure 2 Schematic diagram of the structure of the device for preparing the second interface layer and the third interface layer. Figure 1 The device shown includes a vacuum chamber 1, a sample stage 2, a DC anode 3, a first target material 4 and a second target material 5; wherein the first target material 4 and the second target material 5 can be adjusted according to actual deposition material requirements.

[0090] In some embodiments, physical vapor deposition includes: under the condition of introducing a mixed gas of argon and nitrogen-containing gas, using a combination of a chromium target and a zirconium target, a chromium-zirconium alloy target or a chromium-zirconium-nitrogen alloy target, sputtering and depositing a second interface layer on at least a portion of the surface of the first interface layer.

[0091] Before forming the first interface layer, the substrate is cleaned. The method for cleaning the substrate can adopt a conventional cleaning method in the technical field (including but not limited to the field of decorative plating).

[0092] In some embodiments, the cleaning treatment of the substrate includes the following steps: placing the substrate in water (such as deionized water) for ultrasonic cleaning for 10 to 15 minutes, vacuum drying the cleaned substrate for 15 to 20 minutes, and placing the substrate on a sample stage in a vacuum chamber of a sputtering coating (such as magnetron sputtering coating) device after drying. The sample stage may be a rotatable sample stage.

[0093] In some embodiments, the temperature of sputtering deposition is 30-330°C, such as can be selected from but not limited to 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 150°C, 200°C, 250°C, 300°C, 330°C or a range consisting of any two thereof.

[0094] In some embodiments, the total gas pressure of the mixed gas is 0.3-1.2 Pa, such as but not limited to 0.3 Pa, 0.5 Pa, 0.8 Pa, 1.0 Pa, 1.2 Pa or a range consisting of any two of them.

[0095] In some embodiments, the nitrogen-containing gas is nitrogen gas, and the gas flow rate of nitrogen gas is 5 to 52 sccm, such as can be selected from but not limited to 5 sccm, 8 sccm, 10 sccm, 15 sccm, 20 sccm, 25 sccm, 30 sccm, 35 sccm, 40 sccm, 45 sccm, 50 sccm, 52 sccm or a range consisting of any two of them.

[0096] In some embodiments, the gas volume ratio of argon and nitrogen in the mixed gas is (2-6) : 1, such as but not limited to 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1 or a range consisting of any two of them.

[0097] It can be understood that argon, nitrogen-containing gas or carbon-containing gas etc. can be introduced into the vacuum chamber through a single path or mixed into the chamber through a mixing cylinder, the purpose of which is to reduce the impurity content of the multifunctional protective coating material of the present invention and improve its performance.

[0098] In some embodiments, when the target material is a combination of a chromium target and a zirconium target, the power density of the chromium target is 1.3 to 6.7 W / cm 2 The power density of the zirconium target is 0.5~7.9W / cm 2 , such as the power density of the chromium target can be selected from but not limited to 1.3 W / cm 2 , 1.5W / cm 2 、1.8W / cm 2 , 2W / cm 2 , 2.5W / cm 2 、3W / cm 2、3.5W / cm 2 , 4W / cm 2 , 4.5W / cm 2 , 5W / cm 2 , 5.5W / cm 2 、6W / cm 2 、6.5W / cm 2 、6.7W / cm 2 or any range consisting of the two, the power density of the zirconium target can be selected from but not limited to 0.5 W / cm 2 , 0.8W / cm 2 , 1W / cm 2 , 1.5W / cm 2 , 2W / cm 2 , 2.5W / cm 2 、3W / cm 2 、3.5W / cm 2 , 4W / cm 2 , 4.5W / cm 2 , 5W / cm 2 , 5.5W / cm 2 、6W / cm 2 、6.5W / cm 2 , 7W / cm 2 , 7.5W / cm 2 、7.9W / cm 2 Or a range consisting of any two of them.

[0099] In some embodiments, when the target material is a chromium-zirconium alloy target or a chromium-zirconium-nitrogen alloy target, the power density of the target material is 4 to 6 W / cm 2 , such as can be selected from but not limited to 4W / cm 2 , 4.5W / cm 2 , 5W / cm 2 , 5.5W / cm 2 、6W / cm 2 Or a range consisting of any two of them.

[0100] In some embodiments, the bias voltage of the substrate is -150 to -20 V, such as but not limited to -150 V, -120 V, -100 V, -80 V, -50 V, -20 V or any two thereof.

[0101] In some embodiments, the sputtering deposition time is 10 to 150 minutes, such as but not limited to 10 minutes, 20 minutes, 50 minutes, 80 minutes, 100 minutes, 150 minutes, or any two thereof. The sputtering deposition time is adjusted according to the thickness of the target second interface layer. The longer the sputtering deposition time is, the thicker the second interface layer is.

[0102] In some embodiments, the background vacuum of the vacuum chamber used for sputtering deposition is ≤3.0×10 -4 Pa. This pressure setting can ensure the collision between the sputtered particles and the gas molecules, and can also reduce the entry of impurities into the gas molecules during the deposition process, so as to improve the corrosion resistance, purity and bonding strength of the material of the present invention.

[0103] In some embodiments, after forming the first interface layer and before forming the second interface layer, the method further includes: polishing the surface of the first interface layer. Furthermore, during the polishing process, the surface glossiness of the first interface layer is ≥500 GU.

[0104] In some embodiments, the preparation method further comprises: depositing constituent elements of the third interface layer on at least a portion of the surface of the second interface layer by vapor deposition to form the third interface layer.

[0105] In some embodiments, the method for forming the third interface layer specifically includes: under the condition of introducing a mixed gas of nitrogen-containing gas and / or carbon-containing gas and argon gas, using a metal single substance target or an alloy target, sputtering and depositing on at least a portion of the surface of the second interface layer to form the third interface layer.

[0106] Another aspect of the present invention provides the use of any one of the above-mentioned composite protective coatings in alloy film products.

[0107] In some embodiments, the composite protective coating is provided as at least a portion of a protective coating of an alloy film article.

[0108] Among them, alloy film products include but are not limited to any one or more of 3C digital products, mobile phone parts, automotive products, aerospace products, light alloy products and pure metal products. 3C digital products may include but are not limited to mobile device parts, wearable parts, vehicle parts, etc.

[0109] Another aspect of the present invention provides an alloy film product, comprising a substrate and any one of the above-mentioned composite protective coatings.

[0110] In some embodiments, the composite protective coating is disposed on at least one side of the substrate.

[0111] In some embodiments, the surface material of the substrate is a light alloy or a pure metal. Further, the light alloy includes at least one of nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based and zinc-based; the pure metal includes at least one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium.

[0112] In some embodiments, the alloy film article includes a single or multiple composite protective coating layers.

[0113] The alloy film product may include only the composite protective coating of the present invention, or may additionally include other film layers. The composite protective coating of the present invention may be used in combination with the other film layers.

[0114] The test method involved in the present invention is as follows:

[0115] 1. Testing and analysis of coating morphology and composition

[0116] The samples to be tested all use silicon wafers as substrates and are tested using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX).

[0117] Morphology analysis: A scanning electron microscope (Regulus 8230, manufactured by Hitachi) was used.

[0118] Composition analysis: An energy dispersive X-ray spectrometer (EDX) attached to a Regulus 8230 scanning electron microscope produced by Hitachi was used, and the relative intensities of all elements were corrected by the ZAF method.

[0119] Test parameters: the electron acceleration voltage is 15 kilovolts, the beam current is 10 microamperes, the sample magnification is 200 times, and each sample is tested at 10 points and the average is taken.

[0120] 2. Nickel release test

[0121] The nickel release test of the composite protective coating of the present invention adopts the EN1811:2011+A1:2015 standard. The working principle is to immerse the tested sample in artificial sweat for (168±2) hours, and use ICP-OES to test the concentration of nickel dissolved in the solution. The nickel release is measured in micrograms per square centimeter per week (μg / cm 2 / week) indicates that nickel release is less than 0.5μg / cm 2 / week is passed, otherwise it is failed. In this test, the detection accuracy MDL (Method Detection Limit) is less than 0.05μg / cm 2 / week, no nickel release was within the detection accuracy, recorded as ND (Not Detected).

[0122] 3. Salt spray corrosion resistance test of composite protective coating

[0123] When the salt spray corrosion resistance test of the composite protective coating of the present invention is conducted, the sample to be tested is a substrate suitable for practical application, and the improvement degree of the corrosion resistance of the substrate by the coating is tested. The surface material of the "substrate suitable for practical application" may include, but is not limited to: aluminum alloy sheet.

[0124] Adopt ASTM B117 salt spray test standard.

[0125] The test cycle of coatings prepared on substrates of different materials can be different:

[0126] The test period for samples containing aluminum alloy matrix is ​​48h;

[0127] The standard for "passing (OK)" salt spray corrosion resistance test is: after the sample is tested, there is no corrosion, discoloration, or rust on the appearance.

[0128] The standard for "failure (NG)" in the salt spray corrosion test is: after the sample is tested, corrosion, discoloration or rust is found on the surface.

[0129] 4. Chromaticity value test of composite protective coating

[0130] When testing the chromaticity value of the composite protective coating, the sample to be tested uses a substrate that is suitable for practical application, and detects the degree of improvement of the coating on the density and other properties of the substrate. The surface material of the "substrate that is suitable for practical application" may include but is not limited to: aluminum alloy.

[0131] The L value, a value and b value of the samples were tested using a CM-3700A-U desktop spectrophotometer produced by Konica Japan. The F2 light source was selected as the light receiving system. Six matrix points were tested for each sample and the average value was taken.

[0132] Among them, the L value represents the brightness value, the a value represents the red and green chromaticity values, and the b value represents the yellow and blue chromaticity values.

[0133] The larger the L value, the higher the brightness, indicating that the coating surface is smoother and more compact. The mechanism is as follows: the spectrophotometer reflects the incident light on the surface of the sample to be tested, and obtains a reflectivity curve. The amplitude of the curve can reflect the smoothness and density of the material, which can be specifically characterized by the L value. For the same material, the higher its smoothness and density, the larger the L value it displays.

[0134] The stainless steel sheets, aluminum alloy sheets and silicon sheets in the following embodiments and comparative examples are made of the same material.

[0135] 5. Hundred-grid test

[0136] The grid test in the composite protective coating embodiment of the present invention is based on the provisions of the G / BT 9278 standard. The specific method is as follows: use a grid knife to scratch 10×10 1mm×1mm small grids on the coating area on the sample surface, and each scribe line penetrates into the glass sample substrate. Use 3M610 adhesive tape to stick to the grid area to squeeze out the bubbles, static pressure for more than 5 seconds, the product remains motionless, and the tape is quickly pulled up at a 90° angle on one side. After the test, the sample surface is observed and the grade is determined according to the provisions of the G / BT 9278 standard, where 5B level means the test is passed and levels below 5B mean failure.

[0137] 6. Gloss test

[0138] The glossiness test of the composite protective coating of the present invention adopts a gloss meter of model ZGM1120 produced by Zehntner Company of Switzerland to test the glossiness of the surface.

[0139] Test parameters: gloss range is 0-2000GU, measurement accuracy is ±1%, angle measurement is 60°, and each sample is tested at 5 matrix points on a flat surface and the average value is taken.

[0140] 7. Diffuse reflectivity of the surface P Rd test

[0141] When testing the diffuse reflection ratio of the composite protective coating, the sample to be tested uses a substrate that is suitable for practical application, and detects the surface roughness of the coating on the substrate. The surface material of the "substrate that is suitable for practical application" may include but is not limited to: aluminum alloy.

[0142] The L value of the sample was tested using a CM-700d1 handheld spectrophotometer produced by Konica Japan. The L value in SCI mode was recorded as L SCI , L value in SCE mode is recorded as L SCE .

[0143] Among them, L SCI The value represents the sum of diffuse reflectance (Rd) and specular reflectance (Rs), that is, the total reflectance, L SCE The value indicates the diffuse reflectance (Rd) value.

[0144] By calculating L SCE / L SCI , that is, the formula: Rd / (Rd+Rs), we can get the proportion of diffuse reflectance (Rd) value to total reflectance value P Rd , recorded as a percentage.

[0145] P RdThe larger the value, the higher the proportion of diffuse reflection, that is, the lower the proportion of specular reflectivity, indicating that the surface is rougher, P Rd The smaller the value, the lower the diffuse reflectance ratio, that is, the higher the specular reflectance ratio, indicating a smoother surface.

[0146] Example 1

[0147] This embodiment provides a composite protective coating, which includes a first interface layer Ni-P material formed on the surface of a substrate, a second interface layer Cr-Zr-N material formed on the surface of the first interface layer, and a third interface layer CrC formed on the surface of the second interface layer.

[0148] The specific preparation method comprises the following steps:

[0149] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0150] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 4 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the first interface layer is completed.

[0151] (3) Fabrication of the second interface layer: Install the Cr target and Zr target in the target position of the vacuum chamber of the coating machine, respectively, and place the sample after the first interface layer is completed into the vacuum chamber of the coating machine. The vacuum chamber is evacuated to 5×10 -4 Pa, heated to 150℃, and kept at constant temperature for 15min. Turn on the sample stage turntable, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 5sccm, set the gas volume to maintain the Ar:N2 gas volume ratio of 6:1, maintain the furnace pressure at 0.6Pa, turn on the bias voltage, set it to -100V, and set the power density of the Cr target to 6W / cm 2 , the power density of the Zr target was set to 1.5 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 300nm.

[0152] (4) Fabrication of the third interface layer: Place the sample coated with the first interface layer and the second interface layer into the vacuum chamber of the coating machine, turn on the sample stage turntable, set the rotation speed to 4 revolutions per minute, adjust the distance from the sample stage to the target surface to 10 cm, use a DC power supply to energize the Cr target, introduce Ar and C2H2 gas, set the Ar gas volume to 30 sccm, set the gas volume ratio of Ar:C2H2 to 3:2, maintain the pressure in the furnace at 0.3 Pa, and set the power density of the Cr target to 3.5 W / cm 2 , depositing a CrC decorative coating, and controlling the film-forming time to obtain a film thickness of 200 nm.

[0153] The aluminum alloy with composite protective coating is obtained by the above method. The chromaticity value of the aluminum alloy sample is tested as follows: L: 32.72, a: 0.51, b: 3.35, which is a dark black decorative coating with an aesthetic effect. The aluminum alloy sample can pass the 48h salt spray test, indicating that the composite protective coating has excellent corrosion resistance; in the hundred-grid test, the result shows that it meets the 5B standard, indicating that the composite protective coating has excellent bonding strength.

[0154] The Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 7%; the aluminum alloy sample was subjected to a nickel release test, and the result showed ND, i.e., no nickel release, which met the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating has excellent nickel release blocking properties.

[0155] The composition of the Cr-Zr-N material of the second interface layer of this embodiment is analyzed, and the composition is Cr 81.6 Zr 13.7 N 4.7 .

[0156] Example 2

[0157] This embodiment provides a composite protective coating, which includes a first interface layer Ni-P material formed on the surface of a substrate, a second interface layer Cr-Zr-N material formed on the surface of the first interface layer, and a third interface layer W and WC formed on the surface of the second interface layer.

[0158] The specific preparation method comprises the following steps:

[0159] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0160] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 4 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the first interface layer is completed.

[0161] (3) Manufacturing of the second interface layer: The first target material 4 in the target position of the vacuum chamber of the coating machine is a CrZr alloy target with an atomic percentage of 65%:35%. The sample after the first interface layer is placed in the vacuum chamber of the coating machine, and the vacuum chamber is evacuated to 5×10 -4 Pa, maintain room temperature (about 30°C) for 15 minutes. Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a radio frequency assisted DC power supply to energize the CrZr alloy target, introduce Ar and N2 gas, set the N2 gas flow rate to 7sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 6:1, maintain the furnace pressure at 0.7Pa, turn on the bias, set it to -100V, and set the power density of the CrZr target to 5W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 300nm.

[0162] (4) Fabrication of the third interface layer: Using a W target, place the sample coated with the first interface layer and the second interface layer into the vacuum chamber of the coating machine, turn on the sample stage turntable, set the speed to 4 revolutions per minute, adjust the distance from the sample stage to the target surface to 10 cm, use a DC power supply to energize the W target, introduce Ar gas, and set the power density of the W target to 3.5 W / cm 2 , keep the pressure in the furnace at 0.5Pa, and obtain a W metal layer with a thickness of 100nm by controlling the film forming time; then introduce Ar and C2H2 gases, set the Ar gas volume to 30sccm, set the gas volume to maintain the Ar:C2H2 gas volume ratio of 3:1, keep the pressure in the furnace at 0.8Pa, turn on the bias voltage, set it to -100V, and set the power density of the W target to 5W / cm 2 , depositing a WC layer, and by controlling the film-forming time, the total film thickness (the total thickness here refers to the thickness of the decorative coating composed of the W metal layer and the WC layer) is 300nm.

[0163] The aluminum alloy with composite protective coating is obtained by the above method. The chromaticity value of the aluminum alloy sample is tested as follows: L: 48.42, a: 0.29, b: 2.54, which is a dark gray decorative coating with an aesthetic effect. The aluminum alloy sample can pass the 48h salt spray test, indicating that the composite protective coating has excellent corrosion resistance; in the hundred-grid test, the result shows that it meets the 5B standard, indicating that the composite protective coating has excellent bonding strength.

[0164] The Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 8.5%; the aluminum alloy sample was subjected to a nickel release test, and the result showed ND, i.e., no nickel release, which met the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating has excellent nickel release blocking properties.

[0165] The composition of the Cr-Zr-N material of the second interface layer of this embodiment is analyzed, and the composition is Cr 61.4 Zr 33.2 N 5.4 .

[0166] Example 3

[0167] This embodiment provides a composite protective coating, which includes a first interface layer Ni-P material formed on the surface of a substrate, a second interface layer Cr-Zr-N material formed on the surface of the first interface layer, and a third interface layer CrSiN formed on the surface of the second interface layer.

[0168] The specific preparation method comprises the following steps:

[0169] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0170] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 4 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the first interface layer is completed.

[0171] (3) Fabrication of the second interface layer: Cr target and Zr target were installed in the target position of the vacuum chamber of the coating machine, and the sample after the first interface layer was placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5×10 -4 Pa, heated to 150℃, and kept at constant temperature for 15min. Turn on the sample stage turntable, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 42sccm, set the gas volume to maintain the Ar:N2 gas volume ratio of 2:1, maintain the furnace pressure at 0.8Pa, turn on the bias voltage, set it to -100V, and set the power density of the Cr target to 3.9W / cm 2 , the power density of the Zr target was set to 1.9 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 300nm.

[0172] (4) Fabrication of the third interface layer: The Zr target was replaced with a Si target, and the samples coated with the first and second interface layers were placed in the vacuum chamber of the coating machine. The sample stage turret was turned on, and the rotation speed was set to 4 revolutions per minute. The distance from the sample stage to the target surface was adjusted to 10 cm. The Cr target and the Si target were powered by a DC power supply, and Ar and N2 gases were introduced. The Ar gas volume was set to 30 sccm, and the gas volume was set to maintain the Ar:N2 gas volume ratio of 3:2. The pressure in the furnace was maintained at 0.3 Pa, and the power density of the Cr target was set to 1.0 W / cm 2 , the power density of the Si target was set to 4.5 W / cm 2 , depositing a CrSiN decorative coating, and controlling the film formation time to obtain a film thickness of 100 nm.

[0173] The aluminum alloy with composite protective coating is obtained by the above method. The chromaticity value of the aluminum alloy sample is tested as follows: L: 74.37, a: -4.52, b: -10.35, which is a bright blue decorative coating with an aesthetic effect. The aluminum alloy sample can pass the 48h salt spray test, indicating that the composite protective coating has excellent corrosion resistance; in the hundred-grid test, the result shows that it meets the 5B standard, indicating that the composite protective coating has excellent bonding strength.

[0174] The Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 8%; the aluminum alloy sample was subjected to a nickel release test, and the result showed ND, i.e., no nickel release, which met the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating has excellent nickel release blocking properties.

[0175] The composition of the Cr-Zr-N material of the second interface layer of this embodiment is analyzed, and the composition is Cr 47.1 Zr 17.4 N 35.5 .

[0176] Example 4

[0177] This embodiment provides a composite protective coating, which includes a first interface layer Ni-P material formed on the surface of a substrate, a second interface layer Cr-Zr-N material formed on the surface of the first interface layer, and a third interface layer TiN formed on the surface of the second interface layer.

[0178] The specific preparation method comprises the following steps:

[0179] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0180] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 4 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the first interface layer is completed.

[0181] (3) Fabrication of the second interface layer: Cr target and Zr target were installed in the target position of the vacuum chamber of the coating machine, and the sample after the first interface layer was placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5×10 -4 Pa, heated to 150℃, and kept at constant temperature for 15min. Turn on the sample stage turntable, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 42sccm, set the gas volume to maintain the Ar:N2 gas volume ratio of 2:1, maintain the furnace pressure at 0.8Pa, turn on the bias voltage, set it to -100V, and set the power density of the Cr target to 4.1W / cm 2 , the power density of the Zr target was set to 1.5 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 300nm.

[0182] (4) Fabrication of the third interface layer: The Cr target was replaced with a Ti target, and the samples coated with the first and second interface layers were placed in the vacuum chamber of the coating machine. The sample stage turret was turned on, and the rotation speed was set to 4 revolutions per minute. The distance from the sample stage to the target surface was adjusted to 10 cm. The Cr target and the Si target were powered by a DC power supply, and Ar and N2 gases were introduced. The Ar gas volume was set to 30 sccm, and the gas volume was set to maintain the Ar:N2 gas volume ratio of 10:1. The pressure in the furnace was maintained at 0.2 Pa, the bias voltage was turned on and set to -150 V, and the power density of the Ti target was set to 3.5 W / cm 2 , a TiN decorative coating is deposited, and the film thickness is 200nm by controlling the film formation time.

[0183] The aluminum alloy with composite protective coating is obtained by the above method. The chromaticity value of the aluminum alloy sample is tested as follows: L: 69.19, a: 2.50, b: 29.67, which is a golden decorative coating with beautiful effect. The aluminum alloy sample can pass the 48h salt spray test, indicating that the composite protective coating has excellent corrosion resistance; in the hundred-grid test, the result shows that it meets the 5B standard, indicating that the composite protective coating has excellent bonding strength.

[0184] The Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 11%; the nickel release test of the aluminum alloy sample showed that the nickel release amount was <0.5μg / cm 2 / week, meeting the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating has excellent nickel release blocking properties.

[0185] The composition of the Cr-Zr-N material of the second interface layer of this embodiment is analyzed, and the composition is Cr 52.0 Zr 12.1 N 35.9 .

[0186] Example 5

[0187] This embodiment provides a composite protective coating, which includes a first interface layer Ni—P material formed on the surface of a substrate and a second interface layer Cr—Zr—N material formed on the surface of the first interface layer.

[0188] The specific preparation method comprises the following steps:

[0189] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0190] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 4 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the first interface layer is completed.

[0191] (3) Fabrication of the second interface layer: Cr target and Zr target were installed in the target position of the vacuum chamber of the coating machine, and the sample after the first interface layer was placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5×10 -4 Pa, heated to 150℃, and kept at constant temperature for 15min. Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 14sccm, set the gas volume to maintain the Ar:N2 gas volume ratio of 3:1, maintain the furnace pressure at 0.7Pa, turn on the bias voltage, set it to -100V, and set the power density of the Cr target to 5W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 3500nm.

[0192] The aluminum alloy with composite protective coating is obtained by the above method. The chromaticity value of the aluminum alloy sample is tested as follows: L: 79.19, a: 0.45, b: 3.82, which is a metallic silver-white decorative coating with an aesthetic effect. The aluminum alloy sample can pass the 48h salt spray test, indicating that the composite protective coating has excellent corrosion resistance; in the hundred-grid test, the result shows that it meets the 5B standard, indicating that the composite protective coating has excellent bonding strength.

[0193] The Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 10.5%; the nickel release test of the aluminum alloy sample showed that the nickel release amount was <0.5μg / cm 2 / week, meeting the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating has excellent nickel release blocking properties.

[0194] The composition of the Cr-Zr-N material of the second interface layer of this embodiment is analyzed, and the composition is Cr 60.9 Zr 26.1 N 13 .

[0195] Example 6

[0196] This embodiment provides a composite protective coating, which includes a first interface layer Ni—P material formed on the surface of a substrate and a second interface layer Cr—Zr—N material formed on the surface of the first interface layer.

[0197] The specific preparation method comprises the following steps:

[0198] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0199] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 3 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the first interface layer is completed.

[0200] (3) Fabrication of the second interface layer: Install the Cr target and Zr target in the target position of the vacuum chamber of the coating machine, respectively, and place the sample after the first interface layer is completed into the vacuum chamber of the coating machine. The vacuum chamber is evacuated to 5×10 -4 Pa, heated to 150℃, and kept at constant temperature for 15min. Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 14sccm, set the gas volume to maintain the Ar:N2 gas volume ratio of 3:1, maintain the furnace pressure at 0.7Pa, turn on the bias voltage, set it to -100V, and set the power density of the Cr target to 5W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 200nm.

[0201] The aluminum alloy with composite protective coating is obtained by the above method. The chromaticity value of the aluminum alloy sample is tested as follows: L: 76.31, a: 0.51, b: 3.41, which is a metallic silver-white decorative coating with an aesthetic effect. The aluminum alloy sample can pass the 48h salt spray test, indicating that the composite protective coating has excellent corrosion resistance; in the hundred-grid test, the result shows that it meets the 5B standard, indicating that the composite protective coating has excellent bonding strength.

[0202] The Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 8.5%; the nickel release test of the aluminum alloy sample showed that the nickel release amount was <0.5μg / cm 2 / week, meeting the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating has excellent nickel release blocking properties.

[0203] The composition of the Cr-Zr-N material of the second interface layer of this embodiment is analyzed, and the composition is Cr 60.9 Zr 26.1 N 13 .

[0204] Example 7

[0205] This embodiment provides a composite protective coating, which includes a first interface layer Ni—P material formed on the surface of a substrate and a second interface layer Cr—Zr—N material formed on the surface of the first interface layer.

[0206] The specific preparation method comprises the following steps:

[0207] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0208] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 7 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the first interface layer is completed.

[0209] (3) Fabrication of the second interface layer: Cr target and Zr target were installed in the target position of the vacuum chamber of the coating machine, and the sample after the first interface layer was placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5×10 -4 Pa, heated to 150℃, and kept at constant temperature for 15min. Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 14sccm, set the gas volume to maintain the Ar:N2 gas volume ratio of 3:1, maintain the furnace pressure at 0.7Pa, turn on the bias voltage, set it to -100V, and set the power density of the Cr target to 5W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 1000nm.

[0210] The aluminum alloy with composite protective coating is obtained by the above method. The chromaticity value of the aluminum alloy sample is tested as follows: L: 79.21, a: 0.41, b: 3.91, which is a metallic silver-white decorative coating with an aesthetic effect. The aluminum alloy sample can pass the 48h salt spray test, indicating that the composite protective coating has excellent corrosion resistance; in the hundred-grid test, the result shows that it meets the 5B standard, indicating that the composite protective coating has excellent bonding strength.

[0211] The Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 8.5%; the nickel release test of the aluminum alloy sample showed that the nickel release amount was <0.5μg / cm 2 / week, meeting the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating has excellent nickel release blocking properties.

[0212] The composition of the Cr-Zr-N material of the second interface layer of this embodiment is analyzed, and the composition is Cr 60.9 Zr 26.1 N 13 .

[0213] Example 8

[0214] This embodiment provides a composite protective coating, which includes a first interface layer Ni-P material formed on the surface of a substrate, a second interface layer Cr-Zr-N material formed on the surface of the first interface layer, and a third interface layer CrSiNC formed on the surface of the second interface layer.

[0215] The specific preparation method comprises the following steps:

[0216] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0217] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 4 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the first interface layer is completed.

[0218] (3) Fabrication of the second interface layer: Cr target and Zr target were installed in the target position of the vacuum chamber of the coating machine, and the sample after the first interface layer was placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5×10 -4 Pa, heated to 150℃, and kept at constant temperature for 15min. Turn on the sample stage turntable, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 42sccm, set the gas volume to maintain the Ar:N2 gas volume ratio of 2:1, maintain the furnace pressure at 0.8Pa, turn on the bias voltage, set it to -100V, and set the power density of the Cr target to 3.9W / cm 2 , the power density of the Zr target was set to 1.9 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 3000nm.

[0219] (4) Fabrication of the third interface layer: The Zr target was replaced with a Si target, and the samples coated with the first and second interface layers were placed in the vacuum chamber of the coating machine. The sample stage turret was turned on, and the rotation speed was set to 4 revolutions per minute. The distance from the sample stage to the target surface was adjusted to 10 cm. The Cr target and the Si target were powered by a DC power supply. Ar, N2, and C2H2 gases were introduced. The Ar gas volume was set to 30 sccm. The gas volume was set to maintain the Ar:N2:C2H2 gas volume ratio of 4:1:3. The pressure in the furnace was kept at 0.3 Pa, and the power density of the Cr target was set to 1.0 W / cm 2 , the power density of the Si target was set to 4 W / cm 2 , depositing CrSiNC decorative coating, and controlling the film forming time to obtain a film thickness of 1500nm.

[0220] The aluminum alloy with composite protective coating is obtained by the above method. The chromaticity value of the aluminum alloy sample is tested as follows: L: 50.37, a: -0.02, b: -1.0, which is a dark gray decorative coating with an aesthetic effect. The aluminum alloy sample can pass the 48h salt spray test, indicating that the composite protective coating has excellent corrosion resistance; in the hundred-grid test, the result shows that it meets the 5B standard, indicating that the composite protective coating has excellent bonding strength.

[0221] The Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 8%; the nickel release test of the aluminum alloy sample showed that the nickel release amount was <0.5μg / cm 2 / week, meeting the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating has excellent nickel release blocking properties.

[0222] The composition of the Cr-Zr-N material of the second interface layer of this embodiment is analyzed, and the composition is Cr 47.1 Zr 17.4 N 35.5 .

[0223] Embodiments 9 to 11

[0224] Examples 9 to 11 refer to the preparation method of Example 8, except that the composition of the second interface layer is different. Cr-Zr-N coatings with different compositions are manufactured by adjusting the power density of Cr and Zr and the amount of N2 gas in the second interface layer. See Table 1 for details.

[0225] Table 1 Composition and process parameters of the second interface layer of Examples 8 to 11

[0226]

[0227] The aluminum alloy with composite protective coating is obtained by the above method. The aluminum alloy sample is subjected to salt spray test, and the aluminum alloy sample can pass the 48h salt spray test, indicating that the composite protective coating has excellent corrosion resistance; in the hundred grid test, the result shows that it reaches the 5B standard, indicating that the composite protective coating has excellent bonding strength.

[0228] The Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 8%; the nickel release test of the aluminum alloy sample showed that the nickel release amount was <0.5μg / cm 2 / week, meeting the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating has excellent nickel release blocking properties.

[0229] Example 12

[0230] This embodiment provides a composite protective coating, which includes a first interface layer Ni—P material formed on the surface of a substrate and a second interface layer Cr—Zr—N material formed on the surface of the first interface layer.

[0231] The specific preparation method comprises the following steps:

[0232] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0233] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, a chemical nickel plating solution is added, wherein the chemical nickel plating solution adopts a conventional low-phosphorus nickel plating solution on the market, and the capacity of the low-phosphorus nickel plating solution accounts for 21%. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the proportion of the low-phosphorus nickel plating solution, a Ni-P coating with different Ni and P ratios is achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 7 μm is deposited on the surface of the aluminum alloy, and its surface is polished to 500GU. At this point, the first interface layer is completed.

[0234] (3) Fabrication of the second interface layer: Install the Cr target and Zr target in the target position of the vacuum chamber of the coating machine, respectively, and place the sample after the first interface layer is completed into the vacuum chamber of the coating machine. The vacuum chamber is evacuated to 5×10 -4 Pa, heated to 150℃, and kept at constant temperature for 15min. Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 14sccm, set the gas volume to maintain the Ar:N2 gas volume ratio of 3:1, maintain the furnace pressure at 0.7Pa, turn on the bias voltage, set it to -100V, and set the power density of the Cr target to 5W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 1000nm.

[0235] The aluminum alloy with a composite protective coating is obtained by the above method. The chromaticity value of the aluminum alloy sample is tested as follows: L: 75.30, a: 0.35, b: 4.31, which is a metallic silver-white decorative coating. Its silver-white luster is not as good as that of Example 7, and its aesthetic performance is average. In the salt spray test, the aluminum alloy sample can pass the 24h salt spray test, and local corrosion is found in the 48h salt spray test, indicating that the composite protective coating has certain corrosion resistance; in the 100-grid test, the results show that it meets the 5B standard, indicating that the composite protective coating has excellent bonding strength.

[0236] The nickel release test of aluminum alloy samples showed that the nickel release amount was less than 0.5 μg / cm 2 / week, meeting the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating has excellent nickel release blocking properties.

[0237] For the Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 3.5%.

[0238] Comparative Example 1

[0239] Comparative Example 1 provides a composite protective coating, which includes a first interface layer Ni—P material formed on the surface of a substrate and a CrC layer formed on the surface of the first interface layer.

[0240] The specific preparation method comprises the following steps:

[0241] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0242] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 4 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the first interface layer is completed.

[0243] (3) CrC layer manufacturing: The sample coated with the first interface layer was placed in the vacuum chamber of the coating machine, the sample stage turntable was turned on, the speed was set to 4 revolutions per minute, the distance from the sample stage to the target surface was adjusted to 8 cm, the Cr target was powered by a DC power supply, Ar and C2H2 gas were introduced, the Ar gas volume was set to 30 sccm, the gas volume was set to maintain the Ar:C2H2 gas volume ratio of 3:2, the furnace pressure was maintained at 0.3 Pa, and the power density of the Cr target was set to 3.5 W / cm 2 , depositing a CrC decorative coating, and controlling the film-forming time to obtain a film thickness of 200 nm.

[0244] The aluminum alloy with composite protective coating is obtained by the above method. The chromaticity value of the aluminum alloy sample is tested as follows: L: 32.31, a: 0.61, b: 3.55, which is a dark black decorative coating with an aesthetic effect. 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 8.5%; the nickel release test of the aluminum alloy sample showed failure, and the nickel release amount was > 0.5 μg / cm 2 / week, exceeding the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating does not have nickel release blocking properties.

[0245] Comparative Example 2

[0246] In comparative example 2, the bare aluminum alloy substrate was polished to a mirror effect with a glossiness of 500 GU for testing.

[0247] The polished aluminum alloy substrate bare chip was subjected to SEM testing. The SEM images are shown in Figure 3 As can be seen from the figure, the surface is uneven, with a large number of pits, convex hulls and other defects, which is a surface with poor flatness. The surface roughness test, that is, the diffuse reflectivity ratio test, shows that the diffuse reflectivity ratio P Rd The value is 10.3%, of which the diffuse reflectivity accounts for a large proportion of the total reflectivity, indicating that the surface is relatively rough.

[0248] Comparative Example 3

[0249] Comparative Example 3 provides a protective coating, which includes a TiN layer formed on the surface of a substrate.

[0250] The specific preparation method comprises the following steps:

[0251] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven before fabricating the TiN layer.

[0252] (2) TiN layer manufacturing: The dried aluminum alloy sheet was placed in the vacuum chamber of the coating machine, a Ti target was used, the sample stage turret was turned on, the speed was set to 4 revolutions per minute, the distance from the sample stage to the target surface was adjusted to 10 cm, the Ti target was powered by a DC power supply, Ar and N2 gas were introduced, the gas volume was set to maintain the Ar:N2 gas volume ratio of 10:1, the pressure in the furnace was maintained at 0.2 Pa, the bias was turned on and set to -150 V, and the power density of the Ti target was set to 3.5 W / cm 2 , a TiN decorative coating is deposited, and the film thickness is 200nm by controlling the film formation time.

[0253] The aluminum alloy with protective coating is obtained by the above method. The chromaticity value of the aluminum alloy sample is tested as follows: L: 66.59, a: 2.30, b: 28.57, which is a golden decorative coating. The color value is darker than the L value of Example 4, indicating that its surface is not smooth enough, resulting in a low L value. The aluminum alloy sample cannot pass the 48h salt spray test and fails in the first 8h salt spray test, indicating that the coating does not have corrosion resistance.

[0254] Comparative Example 4

[0255] Comparative Example 4 provides a composite protective coating, which includes a first interface layer Ni-P material formed on the surface of the substrate, a second interface layer Cr-N material formed on the surface of the first interface layer, and a third interface layer CrC formed on the surface of the second interface layer.

[0256] The specific preparation method comprises the following steps:

[0257] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0258] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 4 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the first interface layer is completed.

[0259] (3) Fabrication of the second interface layer: Install a Cr target in the target position of the vacuum chamber of the coating machine, place the sample after the first interface layer is completed in the vacuum chamber of the coating machine, and evacuate the vacuum chamber to 5×10 -4 Pa, heated to 150℃, constant temperature for 15min. Turn on the sample stage turntable, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8cm, use RF-assisted DC power supply to energize the Cr target, introduce Ar and N2 gas, set the N2 gas flow rate to 5sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 6:1, maintain the furnace pressure at 0.6Pa, turn on the bias voltage, set it to -100V, and set the power density of the Cr target to 6W / cm 2 , depositing a Cr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 300nm.

[0260] (4) Fabrication of the third interface layer: Place the sample coated with the first interface layer and the second interface layer into the vacuum chamber of the coating machine, turn on the sample stage turntable, set the rotation speed to 4 revolutions per minute, adjust the distance from the sample stage to the target surface to 10 cm, use a DC power supply to energize the Cr target, introduce Ar and C2H2 gas, set the Ar gas volume to 30 sccm, set the gas volume ratio of Ar:C2H2 to 3:2, maintain the pressure in the furnace at 0.3 Pa, and set the power density of the Cr target to 3.5 W / cm 2 , depositing a CrC decorative coating, and controlling the film-forming time to obtain a film thickness of 200 nm.

[0261] The aluminum alloy with a composite protective coating is obtained by the above method. 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 7%; the nickel release test of the aluminum alloy sample showed failure, and the nickel release amount was > 0.5 μg / cm 2 / week, exceeding the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating does not have nickel release blocking properties.

[0262] Comparative Example 5

[0263] Comparative Example 5 provides a composite protective coating, which includes a first interface layer Ni-P material formed on the surface of the substrate, a second interface layer Zr-N material formed on the surface of the first interface layer, and a third interface layer CrC formed on the surface of the second interface layer.

[0264] The specific preparation method comprises the following steps:

[0265] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven to prepare the first interface layer.

[0266] (2) Manufacturing of the first interface layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 4 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the first interface layer is completed.

[0267] (3) Fabrication of the second interface layer: Install a Zr target in the target position of the vacuum chamber of the coating machine, place the sample after the first interface layer is completed in the vacuum chamber of the coating machine, and evacuate the vacuum chamber to 5×10 -4 Pa, heated to 150℃, constant temperature for 15min. Turn on the sample stage turntable, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8cm, use RF-assisted DC power supply to energize the Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 5sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 6:1, maintain the furnace pressure at 0.6Pa, turn on the bias voltage, set it to -100V, and set the power density of the Zr target to 5W / cm 2 , a Zr-N alloy coating is deposited, and the film thickness is 300nm by controlling the film formation time.

[0268] (4) Fabrication of the third interface layer: Place the sample coated with the first interface layer and the second interface layer into the vacuum chamber of the coating machine, turn on the sample stage turntable, set the rotation speed to 4 revolutions per minute, adjust the distance from the sample stage to the target surface to 10 cm, use a DC power supply to energize the Cr target, introduce Ar and C2H2 gas, set the Ar gas volume to 30 sccm, set the gas volume ratio of Ar:C2H2 to 3:2, maintain the pressure in the furnace at 0.3 Pa, and set the power density of the Cr target to 3.5 W / cm 2 , depositing a CrC decorative coating, and controlling the film-forming time to obtain a film thickness of 200 nm.

[0269] The aluminum alloy with a composite protective coating is obtained by the above method. 1-x P x) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 7%; the nickel release test of the aluminum alloy sample showed failure, and the nickel release amount was > 0.5 μg / cm 2 / week, exceeding the EN1811:2011+A1:2015 nickel release standard, indicating that the composite protective coating does not have nickel release blocking properties.

[0270] Comparative Example 6

[0271] Comparative Example 6 provides a protective coating including a Ni—P material layer formed on the surface of a substrate.

[0272] The specific preparation method comprises the following steps:

[0273] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven before manufacturing the Ni-P material layer.

[0274] (2) Manufacturing of Ni-P material layer: First, pure water is added to the chemical tank, wherein the capacity of pure water accounts for 79% of the total capacity of the chemical tank. Then, common commercially available Amet high-phosphorus nickel plating solutions with brands 1151A, 1151B and 1151C are added in sequence, wherein the sum of the capacities of the chemical nickel plating solutions accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of 1151A, 1151B and 1151C, Ni-P coatings with different Ni to P ratios are achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 7 μm is deposited on the surface of the aluminum alloy, and the surface is polished to 500GU. At this point, the Ni-P material layer is completed.

[0275] The aluminum alloy with Ni-P coating was obtained by the above method. The aluminum alloy sample was subjected to SEM test, and the SEM picture is shown in Figure 4 The SEM image shows that the interface is smooth. The surface glossiness test shows that the surface glossiness is 500GU, which is a smooth and glossy coating, indicating that the Ni-P material layer is polishable. In the 100-grid test, the result shows that it reaches the 5B standard, indicating that it has excellent bonding strength. The surface roughness test, that is, the diffuse reflectivity ratio test, shows that the diffuse reflectivity ratio P Rd The value is 1.6%, which means that the diffuse reflectivity accounts for a very small proportion of the total reflectivity, indicating that the surface is relatively smooth.

[0276] The Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 8.5%.

[0277] Comparative Example 7

[0278] Comparative Example 7 provides a protective coating including a Ni—P material layer formed on the surface of a substrate.

[0279] The specific preparation method comprises the following steps:

[0280] (1) Pretreatment: Aluminum alloy sheet samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 min and then dried in a baking oven before manufacturing the Ni-P material layer.

[0281] (2) Manufacturing of Ni-P material layer: First, pure water is added to the chemical tank, wherein the capacity of the pure water accounts for 79% of the total capacity of the chemical tank. Then, a chemical nickel plating solution is added, wherein the chemical nickel plating solution adopts a commercially available conventional low-phosphorus nickel plating solution. Chemical nickel plating concentrate A and chemical nickel plating concentrate B are added, wherein the capacity of the low-phosphorus nickel plating solution accounts for 21% of the total capacity of the chemical tank. The chemical tank is heated to 90±10°C and maintained at a constant temperature. The dried aluminum alloy sheet is placed in the chemical plating tank. By adjusting the ratio of the low-phosphorus nickel plating solution, a Ni-P coating with different Ni and P ratios is achieved. Finally, by controlling the deposition time, a Ni-P coating with a thickness of 7 μm is deposited on the surface of the aluminum alloy, and its surface is polished to 500GU. At this point, the Ni-P material layer is completed.

[0282] The aluminum alloy with Ni-P coating was obtained by the above method. The aluminum alloy sample was subjected to SEM test, and the result showed that it reached 5B standard in the hundred-grid test, indicating that it had excellent bonding strength.

[0283] The Ni-P material (Ni 1-x P x ) was subjected to EDX composition analysis by weight percentage, and the test results showed that x was 3.5%. The surface roughness test of the aluminum alloy sample, i.e., the diffuse reflectivity ratio test, showed that the diffuse reflectivity ratio P Rd The value is 4.8%, indicating that the ratio of diffuse reflectivity to total reflectivity is relatively higher than that of high-phosphorus nickelide coating, indicating that the surface is rougher than that of high-phosphorus nickelide coating. The reason for this is that the coating of low-phosphorus nickelide is characterized by high hardness and better wear resistance than that of high-phosphorus nickelide, which increases the difficulty of polishing. After polishing, its surface smoothness is not as good as that of high-phosphorus nickelide.

[0284] The composite protective coating of the present invention has high corrosion resistance and can ensure the flatness of the coating surface, so that the product has aesthetic characteristics; at the same time, the present invention can achieve the nickel release blocking effect of the nickel-containing coating. The composite protective coating of the present invention can be directly applied to the surface of a substrate such as an aluminum alloy, and can also be used together with other coatings as a transition layer between a substrate such as an aluminum alloy and other coatings, giving the alloy film product excellent corrosion resistance and aesthetics.

[0285] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite protective coating, characterized in that: It includes a first interface layer containing Ni-P material and a second interface layer containing Cr-Zr-N material.

2. The composite protective coating according to claim 1, characterized in that: The chemical formula of the Ni-P material is Ni 1-x P x , where 7%≤x≤12%, x is the mass percentage; Preferably, the ratio of the diffuse reflectivity value of the first interface layer to the total reflectivity is P Rd ≤5%; where the total reflectivity is the sum of diffuse reflectivity and specular reflectivity.

3. The composite protective coating according to claim 1, characterized in that: The chemical formula of the Cr-Zr-N material is (Cr a Zr b N c )M y , M is a doping element, wherein a, b, c and y are each independently an atomic ratio, a, b, c are positive numbers between 0 and 100, c≤55.1, and 0≤y / (a+b+c+y)≤0.05, a+b+c+y=100; Preferably, 4.7≤c≤55.

1.

4. The composite protective coating according to claim 1, characterized in that: Having at least one of the following characteristics: (1) The thickness of the first interface layer is 0.5 to 10 μm; (2) The thickness of the second interface layer is 0.05 to 6 μm.

5. The composite protective coating according to claim 1, characterized in that: The composite protective coating further comprises a third interface layer; the third interface layer is a decorative coating; in the composite protective coating, the first interface layer, the second interface layer and the third interface layer are arranged in sequence; Preferably, the third interface layer comprises a material containing at least one of Ti, Cr, Si and W; Preferably, the material is at least one of a simple substance, a nitride, a carbide and a carbonitride.

6. The method for preparing the composite protective coating according to any one of claims 1 to 5, characterized in that: The steps include: Forming a first interface layer on at least a portion of the surface of the substrate by chemical plating; Depositing constituent elements of the second interface layer on at least a portion of the surface of the first interface layer by vapor deposition to form a second interface layer; Preferably, the vapor deposition is physical vapor deposition; Preferably, the physical vapor deposition includes: under the condition of introducing a mixed gas of argon and nitrogen-containing gas, using a combination of a chromium target and a zirconium target, a chromium-zirconium alloy target or a chromium-zirconium-nitrogen alloy target, sputtering and depositing on at least a portion of the surface of the first interface layer to form the second interface layer.

7. The method for preparing the composite protective coating according to claim 6, characterized in that: The sputtering deposition conditions include at least one of the following features: (1) The temperature of sputtering deposition is 30-330°C; (2) The total gas pressure of the mixed gas is 0.3-1.2 Pa; (3) The nitrogen-containing gas is nitrogen gas, and the gas flow rate of the nitrogen gas is 5 to 52 sccm; (4) The nitrogen-containing gas is nitrogen, and the gas volume ratio of argon to nitrogen in the mixed gas is (2-6):1; (5) When the target material is a combination of a chromium target and a zirconium target, the power density of the chromium target is 1.3 to 6.7 W / cm 2 The power density of the zirconium target is 0.5~7.9W / cm 2 ; (6) When the target material is a chromium-zirconium alloy target or a chromium-zirconium-nitrogen alloy target, the power density of the target material is 4 to 6 W / cm 2 ; (7) The bias voltage of the substrate is -150 to -20 V; (8) The sputtering deposition time is 10 to 150 minutes; (9) The background vacuum of the vacuum chamber used for sputtering deposition is ≤3.0×10 -4 Pa.

8. The method for preparing the composite protective coating according to claim 6, characterized in that: Also includes at least one of the following features: (1) After forming the first interface layer and before forming the second interface layer, the method further comprises: performing a polishing process on the surface of the first interface layer; (2) during the polishing process, until the surface glossiness of the first interface layer reaches ≥500 GU; (3) depositing constituent elements of the third interface layer on at least a portion of the surface of the second interface layer by vapor deposition to form a third interface layer; (4) The method for forming the third interface layer specifically includes: under the condition of introducing a mixed gas of nitrogen-containing gas and / or carbon-containing gas and argon gas, using a metal single substance target or an alloy target, sputtering and depositing on at least a portion of the surface of the second interface layer to form the third interface layer.

9. Use of the composite protective coating according to any one of claims 1 to 5 or the composite protective coating prepared by the preparation method of the composite protective coating according to any one of claims 6 to 8 in alloy film products; Preferably, the composite protective coating serves as at least a part of the protective coating of the alloy film product.

10. An alloy film product, characterized in that: A composite protective coating comprising a substrate and the composite protective coating according to any one of claims 1 to 5 or a composite protective coating prepared by the preparation method of the composite protective coating according to any one of claims 6 to 8; Preferably, the composite protective coating is located on at least one side of the substrate; Preferably, the surface material of the substrate is a light alloy or pure metal.